2017
DOI: 10.1042/bsr20170806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TNF -308 G>A (rs1800629) gene polymorphism in modulation of leprosy risk: a reappraise meta-analysis of 14 case–control studies

Abstract: Purpose: Earlier studies have shown that tumor necrosis factor (TNF) -308 G>A (rs1800629) gene polymorphism is implicated in the susceptibility to leprosy, but results were inconsistent.Methods: A meta-analysis of 14 studies involving 3327 leprosy cases and 3203 controls was performed to appraise the association of TNF -308 G>A polymorphism with leprosy using MEDLINE (PUBMED), EMBASE, and Google Scholar web databases.Results: Overall, no significant association was observed in allelic (A vs. G: P=0.068; OR = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Moreover, the most frequently involved SNP of TNF in infectious diseases, TNF-308 G>A (rs1800629), has been widely studied in leprosy with different ethnicities, including Nepalese, Brazilians, and Indians (115,141,142). However, these studies obtained inconsistent results for the association of TNF-308 G>A with leprosy, which inspired a meta-analysis of 14 studies on this topic (143). The meta-analysis found that no association was observed in the overall population or in Asians, but TNF-308 G>A showed a protective effect against leprosy risk in the Latin American population (143).…”
Section: Roles Of Cytokine Gene Polymorphisms In Leprosymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the most frequently involved SNP of TNF in infectious diseases, TNF-308 G>A (rs1800629), has been widely studied in leprosy with different ethnicities, including Nepalese, Brazilians, and Indians (115,141,142). However, these studies obtained inconsistent results for the association of TNF-308 G>A with leprosy, which inspired a meta-analysis of 14 studies on this topic (143). The meta-analysis found that no association was observed in the overall population or in Asians, but TNF-308 G>A showed a protective effect against leprosy risk in the Latin American population (143).…”
Section: Roles Of Cytokine Gene Polymorphisms In Leprosymentioning
confidence: 99%
“…However, these studies obtained inconsistent results for the association of TNF-308 G>A with leprosy, which inspired a meta-analysis of 14 studies on this topic (143). The meta-analysis found that no association was observed in the overall population or in Asians, but TNF-308 G>A showed a protective effect against leprosy risk in the Latin American population (143). For LTA of this region, a fine linkage disequilibrium mapping study discovered that LTA+80 A allele was significantly associated with leprosy risk (144).…”
Section: Roles Of Cytokine Gene Polymorphisms In Leprosymentioning
confidence: 99%
“…Studies with monozygotic/dizygotic twins, family, population-based designs, and more recently, genome-wide association studies (GWAS) and whole exome sequencing (WES) have pinpointed single nucleotide polymorphisms (SNPs) in genes that have been consistently replicated in different populations [2][3][4][5][6]. There is evidence that NOD2, LRRK2, TLR1, TNF, IFNG, IL10, IL23R, TYK2 and PACRG/PRKN (formerly PARK2), which are genes that participate in autophagy and recognition pathways, regulating the host innate immune response are associated with leprosy susceptibility, reaction or its clinical forms [6][7][8][9][10][11][12][13][14][15][16][17][18]. However, genetic association of SNPs in major genes that modulate the immune response need independent replication in different ethnic groups to confirm leprosy outcome [19].…”
Section: Introductionmentioning
confidence: 99%
“…falciparum infection such as host genetic polymorphisms [2, 8, 9]. Tumour necrosis factor (TNF) (rs1800629) [previously known as TNF‐α or TNFA] [10] polymorphism is thought to be a critical factor in malaria pathogenesis and in the control of parasitaemia [11]. TNF is a pleiotropic cytokine that acts as a pyrogenic and pro‐inflammatory molecule, produced as a part of the host defence against the infection and is involved in the killing of P. falciparum .…”
Section: Introductionmentioning
confidence: 99%
“…The more common and ancestral TNF1 allele, also referred to as 308.1 allele, has a guanine (G) residue, whereas the less common or alternative allele TNF2 allele, also referred to as 308.2, has an adenine (A) at position 308 of rs1800629 gene promoter. The alternate allele TNF2 has previously been associated with particular manifestations of infectious and non‐infectious diseases [10]. This raises the question of whether variation in the TNF (rs1800629) polymorphism may explain differences in phenotypes related to malaria infections.…”
Section: Introductionmentioning
confidence: 99%